Insurance market density and economic growth in Eurozone countries: the granger causality approach - Rudra P. Pradhan; Saurav Dash; Rana Pratap Maradana; Manju Jayakumar; Kunal Gaurav (Financial Innovation, 2017)
Background: This study examines the relationship between insurance market density (IMD) and economic growth. Methods: We employed Granger causality technique in 19 Eurozone countries for the period 1980-2014. We use three different indicators of IMD, namely life insurance density, non-life insurance density, and total insurance density. We particularly emphasize on whether Granger causality runs between IMD and economic growth both ways, one way, or not at all. Results: Our empirical result recognizes the presence of both unidirectional and bidirectional causality between insurance market density and economic growth. However, these results are mostly non-uniform across Eurozone countries. Conclusions: This study holds important policy implications- economic policies should recognize the differences in the insurance market density and economic growth in order to maintain sustainable economic growth in the Eurozone.
Keywords: L96; O32; O33; O43; 650; Insurance market density; Economic growth; Granger causality; Eurozone countries